Reducing Fracture Risk Adjacent to a Plate With an Angulated Locked End Screw. Issue 11 (November 2015) - Peck, Jeffrey B.; Charpentier, Paul M.; Flanagan, Brian P.; Srivastava, Ajay K.; Atkinson, Patrick J.
Abstract : Objectives: Locking screws often are used in the treatment of osteoporotic fractures. Studies show that locking screws can increase bone stresses at the plate end, which increases the possibility of peri-implant fracture. This study evaluates whether the technique used to insert the end screw is related to the fracture tolerance adjacent to the plate. Methods: Twelve groups of plate constructs were evaluated using a fibular diaphyseal surrogate with mechanical properties similar to osteoporotic bone. All inboard screws were nonlocked with only the end screw fixation differing among groups. The end screws were inserted either perpendicularly to the plate or at an angle of 30 degrees for 6- and 12-hole plates. For both orientations, the end screws were inserted nonlocked, locked, or by a locked overdrilling technique, resulting in 6 groups per plate length. The perpendicular nonlocked screws represented a control group. The constructs were tested to failure in 4-point bending to determine peak load, failure energy, and stiffness. Results: All constructs failed by peri-implant fracture along a plane through the 2 cortical holes of the end screw. Compared with the control group, an angulated locked screw at the plate end significantly increased the peak bending moment and energy required to produce a fracture for both plate lengths (6-hole, P = 0.008, P < 0.001; 12-hole, P = 0.006, P < 0.001). Conclusions: The use of an angulated locked end screw may enhance the resistance of osteoporotic bone to peri-implant fractures caused by bending forces.